2017
DOI: 10.2134/itsrj2016.06.0468
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Turf‐Type Bahiagrass (Paspalum notatum Flügge) Lines for Root and Shoot Traits under Various Nitrogen Regimes

Abstract: Water and fertilizer regulations in Florida have created a market for low‐maintenance grasses. The objectives of this study were to compare rooting and turf performance of three selected turf‐type bahiagrass lines (‘M36’, ‘WEMS12’, and ‘FLDW51’), in comparison with ‘Wilmington’ and ‘Argentine’ bahiagrass, and ‘Floratam’ St. Augustinegrass, grown under three nitrogen (N) rates (49, 98, and 196 kg N ha−1). The experiment was conducted during the summer and fall 2014 in a greenhouse located at the Genetics and Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Therefore, turfgrass, with a narrow to medium leaf texture, is an ideal candidate for breeding programs use (Steketee et al 2017). Pereira et al (2017) stated that a finer leaf texture is preferred and has the potential to use grass in high-value landscapes, while Głąb et al (2015) reported that leaf width and leaf area are indicators of turfgrass resistance to drought stress. Mowing affects leaf texture; after mowing three times, the seashore paspalum leaf texture became smoother, on average, from 3.83 mm to 3.32 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, turfgrass, with a narrow to medium leaf texture, is an ideal candidate for breeding programs use (Steketee et al 2017). Pereira et al (2017) stated that a finer leaf texture is preferred and has the potential to use grass in high-value landscapes, while Głąb et al (2015) reported that leaf width and leaf area are indicators of turfgrass resistance to drought stress. Mowing affects leaf texture; after mowing three times, the seashore paspalum leaf texture became smoother, on average, from 3.83 mm to 3.32 mm.…”
Section: Discussionmentioning
confidence: 99%
“…One water conservation practice is selecting drought‐tolerant turfgrasses with low input characteristics for use in landscapes and on golf courses. Bahiagrass, a warm‐season grass native to South America, is adapted to sandy soils, low fertility, and drought conditions (Burton, 1943; Parodi, 1937; Trenholm et al., 2003), due, in part, to its broad, deep root system (Acuña et al., 2010; Burton, 1943; Huang, 1999; Pereira et al., 2017; Rios et al., 2017; Rios et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Breeders at the University of Florida identified eight promising new lines with superior turf qualities. These accessions have improved density, darker green color, and fewer seedheads compared to their parental lines (Pereira et al., 2017; Rios et al., 2013; Rios et al., 2017), however, their drought tolerance remains unknown. The first objective of this study was to evaluate the performance of turf‐type experimental bahiagrass genotypes to simulated drought conditions compared to the industry standards.…”
Section: Introductionmentioning
confidence: 99%
“…An apomictic mode of reproduction is a barrier to conventional breeding (Rios et al 2017). However, mutagenesis (i.e., using x-rays, gamma-rays, and ethyl methanesulfonate) is a method to create genetic variants in bahiagrass (Kannan et al 2015;Pereira et al 2017). Using mutagenesis as a breeding technique, researchers at the University of Florida developed nine new lines with improved density, darker green color, and fewer seedheads compared to their parental lines (Pereira et al 2017;Rios et al 2013).…”
Section: Introductionmentioning
confidence: 99%